Revisiting Network I/O APIs: The Netmap Framework. (Communications of the ACM, 2012)
The article focuses on the netmap framework input/output application programming interface. It states that netmap can move data traffic up to 40 times faster than existing operating systems and eliminates much unnecessary overhead. It mentions that previous operating systems such as Windows and Linux are influenced by design decisions from almost 30 years ago due to the scarcity of memory and hardware limitations in the network interface controller (NIC). It talks about how modern NICs are able to send or receive packets that are split into multiple memory buffers and use descriptors simpler than those used by the operating system. It comments on the effect latency has on performance and also talks about data structures used to support communication between applications and the kernel.